The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/jopr.13723
|View full text |Cite
|
Sign up to set email alerts
|

Screw‐retained ceramic‐veneered/monolithic zirconia partial implant‐supported fixed dental prostheses: A 5 to 10‐year retrospective study on survival and complications

Yifan Zhang,
Jia Luo,
Ping Di
et al.

Abstract: PurposeTo assess the clinical performance of screw‐retained, ceramic‐veneered, monolithic zirconia partial implant‐supported fixed dental prostheses (ISFDP) over 5–10 years and to evaluate implant‐ and prosthesis‐related factors influencing treatment failure and complications.Materials and methodsPartially edentulous patients treated with screw‐retained all‐ceramic ISFDPs with 2–4 prosthetic units with a documented follow‐up of ≥5 years after implant loading were included in this retrospective study. The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…When the fragile‐veneered area, such as the marginal ridge and cusp, are subjected to increased bite force (often occurring on the position of the first molar), chipping is more likely to occur with greater frequency and ease. Considering aesthetics and function, it is suggested that partial veneers retaining the functional occlusal area as zirconia may be a better option than conventional full‐coverage ones (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…When the fragile‐veneered area, such as the marginal ridge and cusp, are subjected to increased bite force (often occurring on the position of the first molar), chipping is more likely to occur with greater frequency and ease. Considering aesthetics and function, it is suggested that partial veneers retaining the functional occlusal area as zirconia may be a better option than conventional full‐coverage ones (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%